Officers’ Subjective Near Miss Notion in Situations of Collision Avoidance at Sea - Rudan, Igor; Komadina, Pavao; Ivče, Renato (Promet - Traffic&Transportation, 2012)
International studies have determined a strong connection between maritime casualties and human error. Most of the studied effects of human factor on casualties in maritime transport are connected to individual ship crew member’s subjective approach to solving the problem. Therefore, the aim of this research was to determine the relationship between different subjective definitions of a near miss in situations of immediate danger of collision for different categories of examinees. The categories of officers and masters with regard to years of service, type of ship they are on board, ship’s size, etc., were considered. Over a period of four years the research was performed on officers and masters (N=234) that attended specialized courses (3 to 6 attendants) on navigation simulators of the Faculty of Maritime Studies in Rijeka. Based on the results obtained by nonparametric tests for small independent samples, certain significant differences with respect to differently defined divisions of the examinees were identified.